EVALUACIÓN FINANCIERA A LA EMPRESA ENRIQUE ULLAURI MATERIALES DE CONSTRUCCIÓN CÍA. LTDA. EN EL CANTÓN CATAMAYO DE LA PROVINCIA DE LOJA. PERIODOS 2013 – 2014. PROPUESTA DE MEJORAMIENTO - Riofrío Valarezo, Verónica Elizabeth (2016)
The "Financial Company Evaluation Enrique Ullauri Co. Building Materials. Ltda. In Catamayo canton of the Province of Loja. Period 2013 - 2014. Improvement Proposal "is framed within the parameters set by the Academic Regulations of the National University of Loja, created in order to establish the economic and financial position for successful managerial decision making of the company. The financial structure yielded information on the participation of the different areas involved in the economic and financial position of the company; He made a vertical and horizontal analysis increases, decreases and the distribution of the figures in the financial statements was determined; applying financial liquidity indicators, indebtedness, profitability and business activity are met; economic and financial performance was analyzed through evaluation measures such as: The Economic Added (EVA), DUPONT System Value, the Balance Point, economic and financial performance, the same that allowed propose alternatives for improvement that lead to increased levels profitability and thus ensure the permanence of the company, these alternatives are reflected in a Financial Assessment report to serve as a guide to owners of the company to take corrective action. 5 In the first instance the methodology consisted of the recognition of the entity under study, aimed at finding the reference point for the formulation of the Financial Evaluation interviews were conducted the manager and staff of the company, obtaining accurate and reliable information in this if the financial statements, the same as they were subjected to procedures of the financial analysis and evaluation measures, they provided quantifiable data and comparison data allowing analysis of the financial implications of the decisions that have been taken in the company.